Akselerasi Kemampuan Berpikir Kritis melalui Model Cooperative Learning Tipe Teams Games Tournament Terintegrasi Media Domino pada SMA Muhammadiyah 1 Semarang - Tasya Frisca Fortuna; Indri Murniawaty (Universitas Hamzanwadi, 2026)
Critical reasoning skills are an essential cognitive dimension in Economics education. However, empirical findings reveal a deficit in student capabilities, particularly in the problem analysis indicator. Responding to this gap, this quasi-experimental study (pretest-posttest control group) examines the effectiveness of the Teams Games Tournament (TGT) Cooperative Learning model assisted by modified domino cards in enhancing critical thinking. The sample was selected via purposive sampling, designating class XI-4 as the experimental group and XI-3 as the control. Data from validated tests were analyzed using the Paired Sample t-Test and N-Gain Score. The results indicated that the experimental group's achievement was significantly superior (p=0.000 < 0.05). The experimental N-Gain reached 65.36% (fairly effective), outperforming the control class at 52.16% (less effective). The most distinctive cognitive improvements in the experimental class occurred in problem-solving (90.62%) and concept connection (90.17%). In conclusion, the integration of TGT and domino gamification effectively breaks instructional passivity, transforms learning into a dynamic analytical discourse, and comprehensively improves students' critical thinking skills.